2008
DOI: 10.1177/1420326x08091957
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Risk of Airborne Transmitted Infection in Hospitals by Use of Hospital Curtains

Abstract: An in-patient suffering from an airborne infectious disease should be properly isolated in a negative-pressure isolation room to prevent hospital-acquired infection. However, before the infectious status is identified by clinical diagnosis, the patient may be assigned to stay with others in a hospital ward with multiple beds. Under these circumstances, there may be a risk of infection of the neighboring patients. Therefore, reasonable infection control measures should be implemented in multi-bed hospital wards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 16 publications
2
31
0
Order By: Relevance
“…Nevertheless, the findings from such studies have been shown to concur with data from other laboratory studies and from outbreaks. The results in this study agree with other studies in more controlled laboratory environments and computational simulations that show the benefits of using partitions between beds to restrict airborne pathogen movement [18,20,38,40,[45][46][47]. In terms of outbreaks, Gustavson's study [50] shows that tracer gas concentrations measured in a children's ward correlated to varicella transmission, while analysis of the 2003 SAR's outbreak in Hong Kong showed that actual transmission patterns compared well to simulations of both indoor [51] and outdoor [52] airflow paths.…”
Section: Replicability and Reliabilitysupporting
confidence: 82%
See 1 more Smart Citation
“…Nevertheless, the findings from such studies have been shown to concur with data from other laboratory studies and from outbreaks. The results in this study agree with other studies in more controlled laboratory environments and computational simulations that show the benefits of using partitions between beds to restrict airborne pathogen movement [18,20,38,40,[45][46][47]. In terms of outbreaks, Gustavson's study [50] shows that tracer gas concentrations measured in a children's ward correlated to varicella transmission, while analysis of the 2003 SAR's outbreak in Hong Kong showed that actual transmission patterns compared well to simulations of both indoor [51] and outdoor [52] airflow paths.…”
Section: Replicability and Reliabilitysupporting
confidence: 82%
“…The partitions were very effective at containing the source which has the potential to protect patients either side of the partition walls. This concurs with early studies in real hospital environments [45,46], laboratory studies with biological aerosols [38] and recent numerical modelling work [20,47].…”
Section: Ward Layoutsupporting
confidence: 69%
“…Since so many bioaerosol generating activities occur behind closed curtains it is possible that curtains may provide a temporary barrier to the transport of potentially infectious particles to other patients, as found by researchers in Hong Kong [30] Simply keeping curtains closed until particles have settled may thereby limit transfer to other patient areas. However even with particles as large as 5µm this could take several hours which is unfeasible.…”
Section: Commode Usementioning
confidence: 99%
“…Consequently this space exposes a gap for potential passage of pathogens, increasing cross transfer susceptibility. Previous numerical simulations have shown that full height partitions may reduce airborne transmission risk [26] and that those curtaining the length of patient beds are more effective than partially extended ones at preventing infection [40,41]. Physical barriers clearly point to effective intervention measures however further evaluation is needed to explore the most appropriate design and the limitations of such an approach.…”
Section: Scenario 3-4: Double-bed Roommentioning
confidence: 99%